2017
DOI: 10.1002/bmc.4094
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory activities and glycerophospholipids metabolism in KLA‐stimulated RAW 264.7 macrophage cells by diarylheptanoids from the rhizomes of Alpinia officinarum

Abstract: Alpinia officinarum is used for its anti-inflammatory activity historically in China. Diarylheptanoids isolated from A. officinarum play important biological roles in the prevention and treatment of inflammatory disorders. Seven diarylheptanoids (1-7) were isolated from A. officinarum. The cell viabilities and anti-inflammatory activities of diarylheptanoids were evaluated by MTT assay and tumor necrosis factor-α production in Kdo2-lipid A-stimulated RAW 264.7 cells in vitro. The relationships between their an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Phosphatidylethanolamine (PE), one product of glycerophospholipid metabolism, is produced through the decarboxylation of Phosphatidylserine (PS) by PS Decarboxylase (PSD) [15]. PS was reported to regulate inflammation and tumor necrosis factor-α (TNF-α) production in Kdo2-lipid A-stimulated RAW 264.7 cells in vitro [16]. Lysophosphatidylethanolamine (LysoPE), the hydrolysate of PE, contributes to cell proliferation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylethanolamine (PE), one product of glycerophospholipid metabolism, is produced through the decarboxylation of Phosphatidylserine (PS) by PS Decarboxylase (PSD) [15]. PS was reported to regulate inflammation and tumor necrosis factor-α (TNF-α) production in Kdo2-lipid A-stimulated RAW 264.7 cells in vitro [16]. Lysophosphatidylethanolamine (LysoPE), the hydrolysate of PE, contributes to cell proliferation and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipid metabolism reportedly played an important role in many chronic inflammatory diseases including psoriasis ( 39 ), Behçet’s disease ( 40 ), and arteriosclerosis ( 41 ). It has been reported that glycerophospholipids might be significantly related to the anti‐inflammatory activities of diarylheptanoids ( 42 ). Taken together, our data indicated CSD led to chronic inflammation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…50 Moreover 48, 50 and 51 displayed moderate inhibitory activity against TNF-α production with 38, 35 and 37% rates respectively at 0.06 mg/mL in Kdo2-lipid (KL) A-stimulated RAW 264.7 macrophages. 60 The numerous studies cited here show that Alpinia officinarum is an important source of diarylheptanoids with proven anti-inflammatory properties.…”
Section: Linear Natural Diarylheptanoidsmentioning
confidence: 89%
“…The same team reported latter that 41 acted against TNF- expression with 43% inhibition rate at 0.05 mg/mL (cell viability >80%) in KLA-stimulated RAW 264.7 macrophages. 60 Following preliminary molecular docking studies, 41 was also proved by Elgazar's team 59 to exhibit cytotoxicity with an IC50 value 26.6 µg/mL and anti-inflammatory activities against IL-1, IL-6 and TNF- expression with 83, 65 and 89 % inhibition rates respectively at 10 µg/mL in LPSinduced HepG2 cells. Investigations on -methoxyketone 42 according to the same experiments than hydroxyketone 41 showed better anti-inflammatory activity with PG biosynthesis inhibition IC50 value of 2.3 µM 50 and reduction of mice TPA-induced ear inflammatory edema with ID50 value of 0.9 µmol/ear (compared to indomethacin : ID50 = 0.9 µmol/ear).…”
Section: Linear Natural Diarylheptanoidsmentioning
confidence: 95%
See 1 more Smart Citation